Differential detection of pathogenic Yersinia spp. by fluorescence in situ hybridization. (April 2017) - Rohde, Alexander; Hammerl, Jens Andre; Appel, Bernd; Dieckmann, Ralf; Al Dahouk, Sascha
Abstract: Yersinia enterocolitica, Y. pseudotuberculosis and Y. pestis are pathogens of major medical importance, which are responsible for a considerable number of infections every year. The detection of these species still relies on cultural methods, which are slow, labour intensive and often hampered by the presence of high amounts of accompanying flora. In this study, fluorescence in situ hybridization (FISH) was used to develop a fast, sensitive and reliable alternative to detect viable bacteria in food. For this purpose, highly specific probes targeting the 16S and 23S ribosomal RNA were employed to differentially detect each of the three species. In order to enable the differentiation of single nucleotide polymorphisms (SNPs), suitable competitor oligonucleotides and locked nucleic acids (LNAs) were used. Starved cells still showed a strong signal and a direct viable count (DVC) approach combined with FISH optimized live/dead discrimination. Sensitivity of the FISH test was high and even a single cell per gram of spiked minced pork meat could be detected within a day, demonstrating the applicability to identify foodborne hazards at an early stage. In conclusion, the established FISH tests proved to be promising tools to compensate existing drawbacks of the conventional cultural detection of these important zoonotic agents. Highlights: Yersinia detection in food by cultural methods is tedious and time-consuming. FISH is an efficient alternative method to detect pathogenic Yersinia. Thermodynamic modelling allows for multiplex FISH assays. Competitors, LNAs and dual stainings make FISH more reliable. DVC-FISH enables superior live/dead differentiation.